MMP-responsive theranostic nanoplatform based on mesoporous silica nanoparticles for tumor imaging and targeted drug delivery. Issue 11 (24th February 2016) - Hu, Jing-Jing; Liu, Li-Han; Li, Ze-Yong; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract : A novel mesoporous silica-based multifunctional theranostic nanoplatform was reported, which can not only achieve MMP-2-activated fluorescence imaging, but also realize tumor targeted drug delivery and drug release indicating. Abstract : In this paper, we report on an intelligent mesoporous silica-based multifunctional theranostic nanoplatform (designated as MMTNP) for tumor imaging as well as controlled drug release. This theranostic nanoplatform consists of MCM-41 typical mesoporous silica nanoparticles (MSNs) as a hydrophobic drug carrier, matrix metalloprotease-2 (MMP-2) activated fluorescence imaging peptides on the surface of MSNs served as diagnostic probes as well as enzyme-responsive nanovalves blocking the pores, and cRGD peptides further functionalized on the surface of MSNs for tumor targeting. In the absence of MMP-2 conditions, the proximity between the fluorescent dye 5(6)-carboxytetramethylrhodamine hydrochloride (TAMRA) and the quencher 4, 4-dimethylamino-azobenzene-4′-carboxylic acid (Dabcyl) on the surface of MSNs resulted in no fluorescence. When the drug loaded nanoplatform arrived at tumor tissue with overexpressed MMP-2, the fluorescence of TAMRA became recovered efficiently due to the hydrolysis of the MMP-2 sensitive peptide substrate, realizing tumor imaging and triggering drug release. In addition, the further introduced cRGD peptide significantly enhanced the targeting efficiency through receptor-mediated endocytosis in tumor cells.